Kingdom of priests a history of Old Testament Israel - Merrill, Eugene H. (Grand Rapids, MI Baker, 1987)
Includes bibliographical references and indexes
Keywords: Bible. O.T. -- history of Biblical events; Jews -- history -- to AD 70.